2016
DOI: 10.15740/has/ijas/12.1/101-105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foliar nutrition of urea and diammonium phosphate on seed yield and economics of sesame (Sesamum indicum L.) under rainfed situation

Abstract: Field experiments were conducted on deep black soil of Mamurabad farm, Oilseed Research Station, Jalgaon (Maharashtra). Sesame cv. JLT-7 was sown during 2008,2009 and 2010 to find out suitable combination of soil and foliar application of urea and diammonium phosphate for seed yield maximization and remunerative treatments. Result revealed that, soil application of RDF + foliar spray of 2 per cent urea twice at flowering and pod formation stages significantly improved the yield attributes viz., number of capsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
5
1
0
Order By: Relevance
“…Thus, it could be concluded that the present recommended dose was not enough to meet the nutrient requirement of sesame under existing agro-climatic condition. The results are in close conformity with those of Malik et al, (2003); Reddy et al, (2005); Singhal et al, (2015); Mahajan et al, (2016); Shubha et al, (2017) and Gujjar et al, (2018). Significantly the highest seed yield (791 kg/ha) was recorded when crop fertilized with 100% RDN + 1% Urea (N 4 ) than all other treatments.…”
Section: Yield Attributes and Yieldsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, it could be concluded that the present recommended dose was not enough to meet the nutrient requirement of sesame under existing agro-climatic condition. The results are in close conformity with those of Malik et al, (2003); Reddy et al, (2005); Singhal et al, (2015); Mahajan et al, (2016); Shubha et al, (2017) and Gujjar et al, (2018). Significantly the highest seed yield (791 kg/ha) was recorded when crop fertilized with 100% RDN + 1% Urea (N 4 ) than all other treatments.…”
Section: Yield Attributes and Yieldsupporting
confidence: 92%
“…Increase in net return and BCR might be due to higher yields and low cost of cultivation. Similar results were obtained by Singhal et al, (2015); Mahajan et al, (2016) and Akhila et al, (2017).…”
Section: Economicssupporting
confidence: 89%
See 1 more Smart Citation
“…Higher availability of nutrients throughout the crop growth, it led to the increased growth and yield attributes resulting in favourable environment for vegetative as well as reproductive crop growth from initial growth stage to harvest, thus enabling the crop for maximum utilization of nutrients, moisture, light and space, which ultimately led to higher seed and stalk yields of sesame. Similar results were obtained by Singhal et al [7], Mahajan et al [12], Vani et al [8] and Gujjar et al [9]. Time of sowing and nutrient management failed to exert any significant influence on the harvest index.…”
Section: Seed and Stalk Yieldsupporting
confidence: 87%
“…Application of nutrients through foliar spray helps in quick regain in drought situation and also prevents loss of nitrogen in different means. Mahajan et al (2016) revealed that foliar with diammonium phosphate significantly improved the yield attributes, number of capsules per plant and oil%. Krishnaprabu and Kalyanasundaram (2007) revealed that foliar spray of 1.5% diammonium phosphate after 40 and 55 days from sowing increased significantly seed yield of sesame and also recorded the highest seed yield (902 kg/ha) compared to the control (470 kg/ha).…”
Section: Introductionmentioning
confidence: 97%